2014
DOI: 10.5539/jas.v6n3p201
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry, GC-MS Analysis, Antioxidant and Antimicrobial Potential of Essential Oil From Five Citrus Species

Abstract: Citrus essential oils were extraction from hydro distillation technique yielding Citrus oil with reasonable yield. Phytochemical screening of all five Citrus oils showed that alkaloids, tannins, sterols, terpenoids, saponoins, flavonoids were present (50-80%). GC/MS analysis showed highest percentage of limonene (58-89%) in Citrus oils. Antioxidant study revealed that Citrus peel oils have strong scavenging activity (83%-91%). Antimicrobial activity was evaluated by agar well method against eight common pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 22 publications
3
15
0
2
Order By: Relevance
“…This activity represents approximately 90% from antioxidant activity of ascorbic acid at 250 ppm and 94% from antioxidant activity of BHT at 200 ppm. These results are in accordance with work of Javed et al (2014) who reported that tangerine have strong scavenging activity (91.1%). Correspondingly, Yang et al (2010) found that citrus peel oil contained limonene which is a major component and having antioxidant activity similar to that of strong antioxidant.…”
Section: Antioxidant Activity Of Tangerine Essential Oilsupporting
confidence: 93%
See 1 more Smart Citation
“…This activity represents approximately 90% from antioxidant activity of ascorbic acid at 250 ppm and 94% from antioxidant activity of BHT at 200 ppm. These results are in accordance with work of Javed et al (2014) who reported that tangerine have strong scavenging activity (91.1%). Correspondingly, Yang et al (2010) found that citrus peel oil contained limonene which is a major component and having antioxidant activity similar to that of strong antioxidant.…”
Section: Antioxidant Activity Of Tangerine Essential Oilsupporting
confidence: 93%
“…Also, it could be noticed that the essential oil of tangerine was soluble in alcohol (90%). Javed et al (2014) reported that the specific gravity and refractive index of tangerine essential oil were 0.86 and 1.465, respectively. However, Bhuyan et al (2015) found that the acid value and the aldehyde content of tangerine essential oil were 0.59 and 2.1%, respectively.…”
Section: Physicochemical Properties Of Tangerine Essential Oilmentioning
confidence: 99%
“…Recently, Adu et al [101] indicated an inhibitory effect of orange juice from fruits at different stages of development against Gram-positive and Gramnegative bacteria and fungi, like B. subtilis NCTC 10073, C. albicans ATCC 10231, E. coli ATCC 25922, P. vulgaris NCTC 4175, Pseudomonas aeruginosa ATCC 27853, and S. aureus ATCC. Similar results on bacteria and fungi were found by Javed et al [121] using essential oils of orange peel.…”
Section: Sweet Orange (Citrus Sinensis (L) Osbeck)supporting
confidence: 88%
“…Citrus essential oil is a kind of essential oil extracted from the peel of citrus, with excellent antibacterial and antioxidant properties (Djenane, 2015;Javed et al, 2014). It is reported that citrus essential oil (1:2 diluted by ethanol) can inhibit the growth of yeast, fungi, spore bacteria, and food toxin-producing bacteria (Deans & Ritchie, 1987).…”
Section: Introductionmentioning
confidence: 99%